Methacrylated Chitosan Based UV Curable Support for Enzyme Immobilization - Bayramoğlu,Gülay (2017)
UV curing is simple, fast and effective procedure for enzyme immobilization with minimized enzymatic activity. UV-curable methacrylated chitosan is here proposed as a support material for immobilization of lipase. The morphology of the polymeric support was characterized by scanning electron microscopy (SEM). Both covalently (CIL) and physically (PIL) immobilized enzyme is analyzed in terms of enzymatic activity as a function of reusability, pH, storage, as well as stability under various experimental conditions. The recovery of activity of lipases immobilized onto a photo-crosslinked polymer network was 82.0% and 70.0% for CIL and PIL, respectively. The optimum pH value for the free lipase was at pH 6.0. The optimum pH of the both CIL and PIL was shifted to pH 7.0. Immobilization increased the thermostability of the lipase from 50 ºC to 62 ºC. The free enzyme lost all its activity within 15 days. Repeated batch experiments show that about 61% of the enzyme activity of CIL and 41% of PIL was retained after 8 cycles.